PENGARUH MOTIVASI DAN KEDISIPLINAN KERJA TERHADAP PRODUKTIVITAS KERJA PEGAWAI PADA PT PLN (PERSERO) AREA PENGATUR DISTRIBUSI (APD) WILAYAH SULSELRABAR KOTA MAKASSAR - Citta, Andi Batary (FAKULTAS ILMU ADMINISTRASI UNIVERSITAS LANCANG KUNING, 2019)
The purpose of this study is to determine how much influence the motivation of employee productivity and to know whether there is influence of work discipline on employee productivity at PT PLN (Persero) Area Distribution Manager Sulselrabar Makassar.The research method used in this research is multiple linear regression analysis with the formula Y = a + b1x1 + b2x2 + e. Results of analysis and discussion obtained significant values for the variable X1 of 0.010 <0.05 and for the variable X2 of 0.047 <0.05 then Ho is rejected and Ha accepted. there is an influence between motivation and work discipline on work productivity. this explains the purpose of this study. and regression model Y = 1.529 + 0.296 x1 + 0.188 x2.Research limititation/implications : This research is only limited to employees of PT PLN (Persero) Distribution Control Area of South Sulawesi, Makassar City.It is suggested for future research to compare also with other regions outside of Makassar so that it will also be known whether there is influence of motivation and discipline on productivity. The research sample was expanded using different parameters and theories.This article gives us an understanding that there is a relationship between motivation and discipline towards employee productivity.